Caldwell-Luc approach for odontogenic maxillary sinusitis - Irfandy, Dolly; Budiman, Bestari Jaka; Ivanny, Putri Sari (PERHATI-KL, 2022)
ABSTRACTBackground: Maxillary odontogenic sinusitis is a maxillary sinusitis of dental origin. Odontogenic origin of infection must be suspected in those sinusitis patients who have symptoms of unilateral maxillary sinusitis, sinonasal symptoms such as nasal obstruction, rhinorrhea, and/or foul odour, a history of dental pain or dental/oral surgical treatment, and in those who are resistant to conventional treatment of sinusitis. Purpose: To report and analyze the result of Caldwell-Luc approach for odontogenic maxillary sinusitis. Case report: One case of odontogenic maxillary dextra sinusitis treated by Caldwell-Luc approach. After 2 months of follow-up, there was no thick and smelly discharge coming out of the nose, no complaints of pain in the nose, nor swelling and numbness of the cheeks and gums. Clinical question: “Does Caldwell-Luc approach provide good result for odontogenic maxillary sinusitis?” Review method: Literature searching was performed through Cochrane database, PubMed, ClinicalKey, and Google Scholar using keywords “Caldwell-Luc” and “odontogenic sinusitis.” Result: The search obtained 76 literatures which were related to clinical question. Afterwards filtered with eligible criteria, had resulted 21 relevant literatures. Conclusion: The choice of Caldwell-Luc approach for treating odontogenic maxillary sinusitis is a less invasive procedure and gave a satisfying result. Overlooking to identify a dental cause of maxillary sinusitis could lead to persistent symptoms, and failure of medical, as well as surgical intervention. ABSTRAKLatar belakang: Sinusitis maksilaris odontogenik adalah sinusitis maksilaris yang bersumber dari infeksi gigi. Sumber infeksi odontogenik harus dipikirkan ketika ditemukan gejala sinusitis maksila unilateral, gejala sinonasal seperti obstruksi hidung, rinorea dan bau busuk, riwayat infeksi gigi sebelumnya, trauma atau karena prosedur bedah pada tatalaksana gigi, dan pada pasien yang resisten terhadap pengobatan konvensional sinusitis. Tujuan: Melaporkan dan menganalisis hasil pendekatan Caldwell-Luc pada kasus sinusitis maksilaris odontogenik. Laporan Kasus: Satu kasus sinusitis maksilaris odontogenik dekstra yang ditatalaksana dengan pendekatan Caldwell-Luc. Setelah 2 bulan follow-up, tidak ada ingus kental dan berbau busuk yang keluar dari hidung, tidak ada keluhan nyeri di hidung, bengkak dan mati rasa pada pipi dan gusi. Pertanyaan klinis: “Apakah prosedur Caldwell-Luc memberikan hasil terbaik untuk kasus sinusitis maksilaris odontogenik?” Telaah literatur: Dilakukan pencarian melalui database Cochrane, PubMed, CinicalKey dan Google Scholar, menggunakan kata kunci “Caldwell-Luc” dan “sinusitis odontogenic”. Hasil: Diperoleh 76 literatur yang terkait dengan pertanyaan klinis. Setelah disaring dengan kriteria riset, terdapat 21 literatur yang relevan. Kesimpulan: Pemilihan tatalaksana sinusitis maksilaris odontogenik dengan pendekatan Caldwell-Luc merupakan prosedur invasif minimal, dan memberikan hasil yang memuaskan. Bila sumber infeksi dari gigi pada sinusitis maksilaris tidak terdeteksi, hal itu akan menyebabkan gejala persisten, dan kegagalan dalam tatalaksana medikamentosa maupun intervensi bedah.